THE URGENCY OF MANAGEMENT STANDARDS IN SUPPORTING QUALITY OF SCHOOL EDUCATION - Ashari, Ria Dwi Rahmawati (Abjadia : International Journal of Education, 2024)
The increasingly discussed quality education in the world of education with national education standards as the foundation. This research aims to determine the importance of management standards in supporting educational quality. This type of research is qualitative with data collection techniques of observation, interviews, and documentation. The research was conducted at Nusantara Islamic High School in Malang City. The results of this study indicate that the program planning at Nusantara Islamic High School has been well implemented, covering short, medium, and long-term programs. The implementation of the work plan in this school has been quite accomplished, but there are some programs that have not been implemented due to several factors. Monitoring and evaluation are carried out every semester, both by the monitoring team and by the school principal related to the implemented programs. Leadership by the principal, who exhibits professionalism, makes educators more focused and gentle in attitude, serving as motivators for students. The information system at Nusantara Islamic High School can utilize technology effectively and serve as an information medium to support the required learning system.